Subordination Method for the Estimation of Certain Subclass of Analytic Functions Defined by the q-Derivative Operator. (19th May 2022) - Rahmatan, Hormoz; Shokri, Ali; Ahmad, Hijaz; Botmart, Thongchai
Abstract : In this paper, we investigate an interesting class of analytic and biunivalent functions in the open unit disk Δ which is defined using the q -derivative operator. We apply the subordination method to the functional of coefficients problem. Furthermore, we obtain the bounds of the certain functional of coefficients for functions in the class H Σ q λ, β, for real and complex parameters. Also, an estimation for the initial Taylor and Maclaurin coefficients of functions in H Σ q λ, α was given.